Formulation and activity test of extract seaweed lip balm ( Sargassum binderi ) and kenanga oil ( Cananga oil ) as lip moisturizer - Apriyani , P; Yunahara , Farida; Faizatun, Faizatun (Annals of Mechnikov’s Institute, 2021)
Introduction: This research is about formulation and activity test of seaweed extract (Sargassum binderi) and sunflower oil kenaga (Cananga oil) as lip moisturizer. The purpose of this study was to utilize natural ingredients and determine the evaluation of lipbalm from seaweed and cananga flower oil which has a function to increase the moisture level of lip. Methods: The formulation of lipbalm was made by three concentrations, formulation 1, formulation 2 and formulation 3. Evaluation was done to test the skin irritation, skin hydration and hedonic test. The method of skin hydration helps to enhancer and moisture the skin by TEWL (transepodermal water loss) tool of derma lab combo. Results: The result of this research showed that all the formulas does not irritate the skin, moisturize and preferred by the panelists. In the third formula, it has a result to increase the humidity of skin within the high significant differences among the three formulas. Conclusion: Therefore, the lip balm formulation increase humidity of skin within the high significant differences among the three formulas. DOI: 10.5281/zenodo.4657825